The Role of Stabilizers in Village Development - Muhammad Jainul Arifin; Ilmi Usrotin Choiriyah (Indonesian Journal of Cultural and Community Development, 2021)
The success of a village development is influenced by one of the roles of the Village Head, thus the role of the Village Head is very important for village development and to increase public awareness to take part in village development. The purpose of this study was to determine the role of the Village Head in development in Keret Village, Krembung District, Sidoarjo Regency. This study focuses on one role theory, namely stabilizers. The method used is qualitative descriptive data obtained through observation, documentation, interviews and using sources from books, journals, and policy documents. The results of this study state that the role of stabilizers in village development in Keret Village. It is still not optimal in terms of development, in terms of stabilizers, it is still trying to improve the development of stabilizers by providing guidance and training to the community so that they can manage and develop rural economic business activities.